Characterizing the May 2015 Karayaylak Glacier surge in the eastern Pamir Plateau using remote sensing - SHANGGUAN, DONGHUI; LIU, SHIYIN; DING, YONGJIAN; GUO, WANQIN; XU, BAIQING; XU, JUNLI; JIANG, ZONGLI (Journal of glaciology, 2016)
We investigate an internal surge of Karayaylak Glacier, which was reported by the media in May 2015. To differentiate the May 2015 glacier surge from other glacier advances, we surveyed changes in velocity, crevasses and glacier area using Landsat 8 OLI L1T, ZY-1-02C and Gaofen-1 images from October 2014 to July 2015. The velocity, measured by automatic feature extraction and tracking during the active phase, was 10–100 times the velocity during the quiescent phase, with a maximum of (20.2 ± 0.9) m d−1 (mean ± standard error) from 8 to 15 May 2015 in the west branch of the glacier. The surge initiation and termination took place from 13 April to 16 June 2015. Ice in the west branch (length, 7 km; area, 6.8 km2) of Karayaylak Glacier accelerated down to the east branch, leading to the development of crevasses and ice covering an additional 0.1 km2 of summer pasture on the northwestern side. However, we detected no advance of the glacier's terminus.